Subjetividades diferenciales en las comunidades locales para la construcción de memoria colectiva - Nemias Gómez Pérez (Cambios y Permanencias, 2017)
Since the beginning of mankind, man has experienced innately belonging to social groups or family nuclei. The above forms groups marked by hereditary / subjective characteristics. Research as "Historical memory for the recovery of the local historical fabric in Ciudad Bolívar" (2014), identify-describe, forms of subjective behavior of local history, forming associations / groups / associations and levels of peculiar affectations. Terms such as "territorial subjectivities" are clarified from the Doctorate in Social Studies of the District University, in the research "Identification of differential subjectivities in women members of the social groups of the barrismo" seeking to give understanding to the application / use in said communities.